Hubungan Paparan Pestisida Kadar Enzim Kolinesterase dengan Kadar Trigliserida pada Pekerja yang Terpapar Pestisida Golongan Organofosfat: Relationship of Pesticide Exposure to Cholinesterase Enzyme Levels with Triglyceride Levels in Workers Exposed to Organophosphate Group Pesticides - Santoso, Andreas Putro Ragil; Wulandari, Devyana Dyah (Medicra (Journal of Medical Laboratory Science/Technology), 2019)
Alzaimer degerative diseases that attack the brain that occur due to several things including cholesterol and poisoning due to organopathic pesticides, cholinesterase. Triglycerides are a part of kolesterol which consists of about 20% of total cholesterol. Pesticide buildup in the body often occurs due to work risks. This study aims to determine how much cholinesterase activity and triglyceride levels are in workers exposed to organophosphate pesticides, and to determine the relationship of pesticide exposure to cholinesterase enzyme levels with triglyceride levels in workers who are exposed to workers exposed to pesticides. This research is an observational research with an experimental approach. The study was conducted at PT.X, which was exposed to 15 pesticides. This study uses a correlation test that will be shown if p <0.05. Based on the results of the study obtained based on the average results of cholinesterase activity obtained at 8,040 U/L while triglycerides at 186 mg/dL. And after the correlation test was obtained at 0.085 indicating that p> 0.05 so it was concluded that there was no relationship between cholinesterase activity with triglyceride levels.